Albumin Use and Its Association with Nutritional Status in the Intensive Care Unit : A Narrative Review - Putu Eka Nantha Kusuma; Jeremy Jonathan; Putu Agus Surya Panji (Udayana University and Indonesian Society of Anesthesiologists (PERDATIN), 2025)
Introduction: Albumin is the major protein in blood plasma that plays a pivotal role in the regulation of oncotic pressure and nutritional status, particularly in critically ill patients. Hypoalbuminemia is frequently observed in ICU patients and is associated with increased morbidity and mortality. This narrative review aims to assess the role and efficacy of albumin supplementation, administered both orally and intravenously, in supporting the nutritional status and prognosis of critically ill patients. Methods: A literature search was conducted across the PubMed, Google Scholar, ScienceDirect, and ProQuest databases utilizing the keywords: